1993
DOI: 10.1002/hep.1840180219
|View full text |Cite
|
Sign up to set email alerts
|

Activin induces cell death in hepatocytes in vivo and in vitro

Abstract: While studying endocrine responses to activin in female rats, we discovered that activin caused a marked reduction in liver mass. The regressed livers exhibited no gross signs of necrosis or infarction, but histopathological evaluation revealed extensive cell death in the centrilobular regions. The dying cells appeared to fragment into structures resembling apoptotic bodies. Liver mass and histological appearance were restored after cessation of activin infusion, indicating that on an organ level, this effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
23
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…For example, activin A can stimulate glycogenolysis (11) and inhibit DNA synthesis in isolated rat hepatocytes in vitro (12). In addition, infusion of activin A into rats caused hepatocellular necrosis around the central vein of the liver (13). These physiologic effects of activin on hepatocytes are consistent with findings that a major site of 125I-labeled activin A binding is the rat liver (14) and that the type II activin receptor is expressed in the mouse liver (ref.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…For example, activin A can stimulate glycogenolysis (11) and inhibit DNA synthesis in isolated rat hepatocytes in vitro (12). In addition, infusion of activin A into rats caused hepatocellular necrosis around the central vein of the liver (13). These physiologic effects of activin on hepatocytes are consistent with findings that a major site of 125I-labeled activin A binding is the rat liver (14) and that the type II activin receptor is expressed in the mouse liver (ref.…”
supporting
confidence: 76%
“…At very early time points, inhibin-deficient mice develop liver pathology that mirrors the known effects of exogenous activins on the liver (13), suggesting that the elevated serum activins, secreted from the tumors, may be causing these aberrations. It is unclear whether the parietal cell depletion and mucosal atrophy are a direct result of the elevated activins or are secondary to the changes in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…These structurally related but functionally diverse polypeptides control the growth and differentiation of many cell types (3)(4)(5). In addition, activins regulate the production of follicle-stimulating hormone and other hormones by the anterior pituitary (6 -8) and have diverse endocrine, paracrine, and autocrine actions throughout the reproductive (9), immune (10,11), hematopoietic (12,13), endocrine (7), and central nervous systems (14). Activins also play key roles in numerous pathophysiologic processes including carcinogenesis (15).…”
mentioning
confidence: 99%
“…12,13) Recent studies have shown that activin A plays several roles in rat liver in vivo and in vitro. [13][14][15][16][17] It inhibits mitogeninduced DNA synthesis in vitro, 14) induces hepatocellular apoptosis in vivo and vitro, [15][16][17] and stimulates glycogenolysis in vitro.…”
mentioning
confidence: 99%